Mitigation of Acid Mine Drainage Using Blended Waste Rock in Near-Equatorial Climates—Geochemical Analysis and Column Leaching Tests - Akihiro Hamanaka; Takashi Sasaoka; Hideki Shimada; Shinji Matsumoto; Ginting Jalu Kusuma; Mokhamad Candra Nugraha Deni (Physchem)
Acid mine drainage (AMD), wherein acidic water is generated from pyrite-containing waste rock, can be mitigated by encapsulating pyritic waste rock with cover materials to restrict the inflow of oxygen and water. However, acidic water inevitably forms during the construction of waste rock dumps before applying cover materials. Considering that the presence of waste rock containing carbonate minerals contributes to acid neutralization, a mixture of carbonate minerals and pyritic waste rock can be utilized to reduce AMD generation before the completion of the cover system as a temporary management strategy. This paper examines waste rock management using blending scenarios. Kinetic NAG and column leaching tests were employed to evaluate the blending ratio necessary to prevent acidic water generation. Geochemical analyses were conducted on rock and leachate samples, including pH and temperature measurements, XRD and XRF analyses, and Ion Chromatography. Consequently, the pH and temperature measurement results obtained during the kinetic NAG test are valuable for expressing the balance between acid generation and acid neutralization by the mixture material. Furthermore, the column leaching test demonstrated that the pH of the leachate remained neutral when the acid generation and acid neutralization reactions were well balanced. Blending waste rocks is an effective method for AMD reduction during the construction of waste rock dumps.